Dystocia Due to Twin Hydrocephalic Fetus in an Osmanabadi Goat - Patil, Anil Dinkarrao; Bhosale , Yogesh Bibhishan (The Indian Journal of Animal Reproduction, 2025)
The hydrocephalic twin in an Osmanabadi goat was reported and smooth delivery was performed using obstetric maneu vers.
Keywords: Dystocia; Hydrocephalic; Osmanabadi Goat; Twin Fetus